CORPORATE GOVERNANCE OF SELECTED PUBLICLY LISTED PHILIPPINE HOTELS - Challoner A. Matero; Marie Jane Jumawan Matero; Eleanor D. Paclijan (UPT Penerbitan Universitas Jember)
Corporate financial scandals and recent financial crises have significantly affected economies and companies worldwide, which renewed emphasis on corporate governance. Mostly, financial performance is still widely used tool for fundamental analysis. This exploratory qualitative research evaluated the corporate governance practices and financial performance of selected publicly listed Philippine hotels in order to present future researches on corporate governance. It discussed the corporate-governance practices of Philippine companies as determined by the OECD scorecard. The financial-performance dimension in comparison to industry average is independently computed. Results showed that publicly listed hotels were not widely held by public investors, the presence of the RPTs that can be classified as financial assistance to entities other than wholly owned subsidiary companies, the need for improvements of environmentally friendly value chains, the nonpublication of relevant information on training and development programs for its employees, and the nondisclosure of the attendance of members of the board of directors in their meetings. Recommendations for future researches were provided.